The Implementation of Flashcards to Improve Students’ Vocabulary Mastery - Rita Budi Styastuti; Pradnya Permanasari (IKIP Siliwangi, 2026)
One of the most important aspects of learning English is expanding one's vocabulary. However, a lot of students still struggle with vocabulary comprehension and mastery, especially when taught using traditional methods. The purpose of this research is to investigate how flashcards can help students become more proficient in vocabulary. This research used a Classroom Action Research (CAR) design with 27 SMK Medika students in 11th grade. The research was carried out over two cycles, each involving planning, action, observation, and reflection. Vocabulary tests (pre-test and post-test), observation, and student questionnaires were used to collect data. The average score improved from 70.26 in the pre-test to 86.7 in Cycle 1 and 98.15 in Cycle 2, showing significant improvements in students' vocabulary mastery. In addition, students demonstrated higher engagement, motivation, and positive attitudes toward the learning process. The use of flashcards helped students understand, master, and use vocabulary more effectively. In conclusion, flashcards are a useful and effective learning tool for enhancing vocabulary mastery in vocational high school students.